2017
DOI: 10.12659/ajcr.903592
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia Telangiectasia in Siblings: Oral Motor and Swallowing Characterization

Abstract: Case seriesPatient: Male, 23 • Female, 20Final Diagnosis: Ataxia telnagiectasiaSymptoms: Gagging • coughing • hoarseness • articulatory inaccuracyMedication: —Clinical Procedure: Oral motor and swallowing assessmentSpecialty: NeurologyObjective:Rare diseaseBackground:The body of literature on oral motor and swallowing disorders in patients with ataxia telangiectasia (AT) is limited.Case Report:The purpose of this study was to characterize oral motor and swallowing disorders in two siblings with AT, based on or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…66 cases (14 studies [ 35 , 226 , 233 , 345 , 431 , 448 , 449 , 463 , 659 , 743 , 768 , 818 , 909 , 916 ]) reported a diagnosis of fatty liver or hepatic steatosis and age of diagnosis was reported in 2 cases (252.0 months and 336.0 months). Seven cases were in the presumed/confirmed variant group and 59 cases were in the presumed/confirmed classical group.…”
Section: Resultsmentioning
confidence: 99%
“…66 cases (14 studies [ 35 , 226 , 233 , 345 , 431 , 448 , 449 , 463 , 659 , 743 , 768 , 818 , 909 , 916 ]) reported a diagnosis of fatty liver or hepatic steatosis and age of diagnosis was reported in 2 cases (252.0 months and 336.0 months). Seven cases were in the presumed/confirmed variant group and 59 cases were in the presumed/confirmed classical group.…”
Section: Resultsmentioning
confidence: 99%
“…12 According to Félix et al 13 , training the inspiratory muscles has a positive effect on the pulmonary function in AT. Also, Rondon-Melo et al 14 stated that oral rehabilitation is needed early in AT. One of the first studies in this area, Unes et al 15 found that 3 months of training consisting of balance and strength exercises and Wii Fit Balance-based video games resulted in significant improvements in AT.…”
Section: Discussionmentioning
confidence: 99%
“…Félix et al14 reported that the inspiratory muscle training is effective on pulmonary functions in the children with AT. Rondon-melo et al25 stated that oral rehabilitation is needed early for children with AT. Apart from these 2 studies, there was no study showing the effectiveness of a physical therapy program, although it has been reported that exercise and physical therapy might minimize the negative effects 15.…”
Section: Discussionmentioning
confidence: 99%